Exploring diazotrophic diversity: unveiling Nif core distribution and evolutionary patterns in nitrogen-fixing organisms - Bruno Thiago de Lima Nichio; Roxana Beatriz Ribeiro Chaves; Fábio de Oliveira Pedrosa; Roberto Tadeu Raittz (BMC Genomics)
Abstract Background Diazotrophs carry out biological nitrogen fixation (BNF) using the nitrogenase enzyme complex (NEC), which relies on nitrogenase encoded by nif genes. Horizontal gene transfer (HGT) and gene duplications have created significant diversity among these genes, making it challenging to identify potential diazotrophs. Previous studies have established a minimal set of Nif proteins, known as the Nif core, which includes NifH, NifD, NifK, NifE, NifN, and NifB. This study aimed to identify potential diazotroph groups based on the Nif core and to analyze the inheritance patterns of accessory Nif proteins related to Mo-nitrogenase, along with their impact on N2 fixation maintenance. Results In a systematic study, 118 diazotrophs were identified, resulting in a database of 2,156 Nif protein sequences obtained with RAFTS³G. Using this Nif database and a data mining strategy, we extended our analysis to 711 species and found that 544 contain the Nif core. A partial Nif core set was observed in eight species in this study. Finally, we cataloged 662 species with Nif core, of which 52 were novel. Our analysis generated 10,076 Nif proteins from these species and revealed some Nif core duplications. Additionally, we determined the optimal cluster value (k = 10) for analyzing diazotrophic diversity. Combining synteny and phylogenetic analyses revealed distinct syntenies in the nif gene composition across ten groups. Conclusions This study advances our understanding of the distribution of nif genes, aiding in the prediction and classification of N₂-fixing organisms. Furthermore, we present a comprehensive overview of the diversity, distribution, and evolutionary relationships among diazotrophic organisms associated with the Nif core. The analysis revealed the phylogenetic and functional organization of different groups, identifying synteny patterns and new nif gene arrangements across various bacterial and archaeal species.The identified groups serve as a valuable framework for further exploration of the molecular mechanisms underlying biological nitrogen fixation and its evolutionary significance across different bacterial lineages.